1983
DOI: 10.1111/j.1476-5381.1983.tb11047.x
|View full text |Cite
|
Sign up to set email alerts
|

Microelectrode recording of the effects of agonists and antagonists on α‐adrenoceptors on rat somatic nerve terminals

Abstract: The effects of apomorphine, catechol, clonidine, isoprenaline, (‐)‐and (±)‐noradrenaline, phenylephrine, pyrogallol and xylazine were investigated on the frequency and amplitude of miniature endplate potentials (m.e.p.ps) and, with the exception of apomorphine, catechol and pyrogallol, on the amplitude of endplate potentials (e.p.ps) in the rat phrenic nerve diaphragm preparation. Clonidine, (‐)‐noradrenaline, phenylephrine and xylazine (each at 1.5 × 10−5M) increased m.e.p.p. frequency but not amplitude. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Both noradrenaline and adrenaline increase the amplitude of the end-plate potential of rat diaphragm muscle; the greater effect occurs with noradrenaline (Kuba, 1970;Kuba and Tomita, 1971). Similar results are obtained with ( -)-noradrenaline and various adrenoceptor agonists (Malta, McPherson, and Raper, 1979;Lim and Muir, 1983). The amplitude of the EJP in frog muscle is likewise increased by noradrenaline (Jenkinson, Stamenovic, and Whitaker, 1968).…”
Section: The Action Of Biogenic Amines On Skeletal Muscle Ejpssupporting
confidence: 68%
“…Both noradrenaline and adrenaline increase the amplitude of the end-plate potential of rat diaphragm muscle; the greater effect occurs with noradrenaline (Kuba, 1970;Kuba and Tomita, 1971). Similar results are obtained with ( -)-noradrenaline and various adrenoceptor agonists (Malta, McPherson, and Raper, 1979;Lim and Muir, 1983). The amplitude of the EJP in frog muscle is likewise increased by noradrenaline (Jenkinson, Stamenovic, and Whitaker, 1968).…”
Section: The Action Of Biogenic Amines On Skeletal Muscle Ejpssupporting
confidence: 68%
“…Authors using relatively high [Ca2+Io (2.5-2.7 mM) were able to obtain a statistically significant increase in MEPP(f) (Kuba, 1970. Lim andMuir, 1983). Others, using up to 2 mM [Ca2'] either did not apply statistics or, in the case of Miyamoto and Breckenridge (19741, found that the increase in MEPP(f) was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Yohimbine blocked not only this effect but also the response to phenylephrine (PE) (Lim and Muir, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…α2-adrenoceptor activation by clonidine and xylazine also caused an increase in MEPP frequency at the rat diaphragm NMJ, and it was eliminated by α-adrenoceptor blockers phentolamine, prazosin and yohimbine, suggesting the presence of presynaptic α1- and α2-adrenoceptors [ 28 ]. Two sympathomimetic agents used in clinical practice, salbutamol and clenbuterol, activated β2-adrenoceptors and induced the elevation of spontaneous ACh secretion in mouse preparations of peroneal nerves and lumbricalis muscles [ 9 , 29 ].…”
Section: Activators and Blockers Of Adrenergic Receptors Alter The Spontaneous Achmentioning
confidence: 99%
“…Snider and Gerald [ 41 ], using a radioenzymatic assay, showed an increase in nerve-stimulated ACh release induced by noradrenaline via presynaptic α1-adrenoceptors. However, noradrenaline did not cause any change in the evoked quantal secretion in the experiments of Lim and Muir [ 28 ], whereas clonidine, phenylephrine and xylazine enhanced EPP amplitude, which was blocked by prazosin and yohimbine. In Chiou and Chang’s [ 42 ] experiments, the EPP quantal content was unaffected by clonidine, although the amplitudes of EPPs and MEPPs were markedly decreased.…”
Section: Sympathomimetic Effects On Ach Quantal Release Evoked By the Nerve Stimulusmentioning
confidence: 99%